Perkawinan Dalam Pandangan Gereja Katolik - Donatus Wea (SEWAGATI: Jurnal Pengabdian Masyarakat Indonesia, 2022)
This article aims to build awareness among community leaders and young people in the Merauke Archdiocese so that they have an adequate understanding of marriage in the Catholic Church with its main aspects. A comprehensive understanding of Catholic marriage will greatly assist Catholics in realizing the noble values of marriage in everyday life. Leaders of the people and young people are expected to be the primary movers in helping God's people to know, learn and understand the rules in the Catholic Church which specifically discuss marriage. In this way, the problems surrounding marriage experienced by couples, for various reasons, can be minimized. The method used is the lecture method, which ends with an in-depth discussion of the material with questions and answers in forums involving all participants and group discussions. Through this activity the participants have sufficient knowledge about the nature of Catholic marriage, the purpose of Catholic marriage; requirements before confirmation of marriage in a catholic manner; canonical hindrances that thwart marriage; and the presence of the tribunal with one of its roles is to assist and protect the couples to continue to maintain the integrity of the marriage bond. Sufficient knowledge about the fundamental aspects of Catholic marriage is an asset for participants to accompany God's people in places of service.